Pengenalan Spora pada Thallophyta (Lumut Kerak) dan Bryophyta (Lumut Daun) - Najmi Azalia Ubaedilah; Neng Sri Mulyani; Pundy Vidiapuri; Rohim Rohim; Ita Fitriyyah (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
This research aims to describe and compare the morphological characteristics of spores in Thallophyta (lichens) and Bryophyta (mosses). The research was conducted at the Biology Laboratory of UIN Sunan Gunung Djati Bandung for one week. This study employed a descriptive method with macroscopic and microscopic observations. Samples of lichens and mosses were analyzed using a light microscope. The results showed that Thallophyta spores have asymmetrical morphology, are pale green, have a count of 15 spores, and are adaptive to extreme conditions. In contrast, Bryophyta spores are round and flat, with a reddish-brown capsule, and a larger number of spores, namely 67. These differences reflect the unique adaptation strategies of the two groups to their respective environments. Lichens, which are a symbiosis between fungi and algae, serve as indicators of environmental quality and grow on various substrates, including polluted areas. Meanwhile, mosses play an important role in maintaining soil moisture, preventing erosion, and supporting water and carbon cycles.